Aplikasi Media Pembelajaran Iqro’ Berbasis Mobile - Yuliani, Eka; Santhi, Komang Hari; Melati, I Gusti Ayu Sri; Sudiatmika, I Putu Gede Abdi (Universitas Tabanan, 2023)
The iqro method is a method of reading the Koran that emphasizes direct reading practice. In each volume there are instructions for learning with the intention of making it easier for everyone who learns and teaches the Koran. At present there are still many Muslims who have not been able to read the Qur'an properly, both from children to adults based on the results of an interview with one of the clerics in the Baitul Mustaqim Jimbaran Mosque said children in 5 -10 years, there are only 5 children who study the mosque. Many factors influence the reduction of children's learning interest in learning iqro. From the above problems an application was made that aims to design and build a mobile-based iqro application for children. The use of technology as a medium for learning as a way out to reduce the number of Muslims who have not been able to read the Qur'an. In making the application, the concept of planning and design through the data collection stage, UML (Unified Modeling Language) and then implementing it. the method used is the MDLC (Multimedia Development Life Cycle) method. The results of this study are iqro learning media applications for mobile-based children as a means of learning the Koran. blackbox testing function of the learning media application iqro runs according to what is displayed in the menus in each application.